2018
DOI: 10.21608/sjfop.2018.17771
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compost and Some Natural Stimulant Treatments On: Ii. Corms Production and Chemical Constituents of (Gladiolus Grandiflorus Cv. Peter Pears) Plants

Abstract: Two field experiments were conducted to investigate the effect of plant compost (0, 2.5, 5.0 and 7.5 ton/fed) and six natural stimulants (green tea extract at 5 g/l, moringa leaves extract at 300 mg/l, garlic extract at 300 mg/l, licorice roots extract at 5 g/l, active dry yeast at 5 g/l and seaweeds extract at 3 cm 3 /l) on corms production and chemical constituents of Gladiolus grandiflorus cv. Peter Pears. The obtained results indicated that corm diameter, number of cormels/plant, dry weight of cormels, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
5
4
0
Order By: Relevance
“…These components play an important role in protecting plant cells from damage and all plant stresses and improving the division of cells and organic food biosynthesis (Kulk, 1995 andStrick et al, 1997). These findings are in accordance with those obtained with regard to the impact of seaweed extracts on growth characteristics (Ragab, 2016 andAbdou et al, 2018). The progressive impact of silicon and seaweed extract on flowering time could be due to their vital role in in balancing the ratio between carbohydrates and nitrogen in favour of flowering (Soliman et al, 2000 andNeumann andZur-Nieden, 2001).…”
Section: Lsd At 5%supporting
confidence: 87%
See 1 more Smart Citation
“…These components play an important role in protecting plant cells from damage and all plant stresses and improving the division of cells and organic food biosynthesis (Kulk, 1995 andStrick et al, 1997). These findings are in accordance with those obtained with regard to the impact of seaweed extracts on growth characteristics (Ragab, 2016 andAbdou et al, 2018). The progressive impact of silicon and seaweed extract on flowering time could be due to their vital role in in balancing the ratio between carbohydrates and nitrogen in favour of flowering (Soliman et al, 2000 andNeumann andZur-Nieden, 2001).…”
Section: Lsd At 5%supporting
confidence: 87%
“…This increase may be due to the existence of certain biochemical compounds such as growth regulators, organic components, macro components and micro components in seaweed extract that may be needed for the induction of antioxidant enzymes responsible for reducing the levels of reactive oxygen species (ROS). The promoting effect of the application of seaweed extract in tagetes plants were found to be similar with those obtained by (Abdou et al, 2018) on gladiolus plants, they found that vegetative growth parameters increased by seaweed extract treatments as compared to control. These findings may be due to the beneficial effect of the availability of naturally occurring nutrients in seaweed extracts, plant growth hormones (auxins, cytokinines and gibberellins) as well as other plant biostimulants, such as amino acids, vitamins that could sustain photosynthetic rates, increase plant resistance, delay plant senescence and regulate cell division (Strick et al, 1997 andHemida et al, 2015).…”
Section: Lsd At 5%supporting
confidence: 74%
“…These results may be attributed to the increase in nutrient elements and/or positive role of organic farmyard manure (FYM) on the physical and chemical properties of the soil, that reflected on the growth and the pigments content. In harmony with these results regarding organic fertilization treatments were those reported by Khalil (2015) and Abdou et al (2018) on gladiolus, El-Naggar and El-Nasharty ( 2009) on Hippeastrum vittatum, Mathivanan et al (2012) on ground nut, Dalawai and Naif (2017) on Dianthus caryophyllus,…”
Section: Chemical Constituents: a Photosynthetic Pigmentssupporting
confidence: 77%
“…These results may be attributed to the increase in nutrient elements and/or positive role of organic fertilizer on the physical and chemical properties of the soil, that reflected on the growth and the pigments content. In harmony with these results regarding organic fertilization treatments were those mentioned by Abdou et al (2013), Khalil (2015), Abdou et al (2018) and Abdou et al (2019) on gladiolus, El-Naggar and El-Nasharty (2009) on Hippeastrum vittatum and Dalawai and Naif (2017) on Dianthus caryophyllus.…”
Section: Photosynthetic Pigmentssupporting
confidence: 70%
“…and some antioxidant (salicylic and ascorbic acids) treatments are among the important agricultural treatments which have been proved to improve corm and cormels production of gladiolus plants. The effect of organic fertilization on increasing corm diameter, number of new cormels and dry weight of corm and cormels of gladiolus were reported by many investigators, such as Ahmed (2013), Abdou et al (2018), Abdou et al (2019) and Karagöz et al (2019) on gladiolus, Kabir et al (2011), Srivastava et al (2014) and Suseela et al (2016) on tuberose, Mirkalae et al (2013) and Prasad et al (2017) on lily, Pandey et al (2017) on dahlia plant who found that compost fertilizer improved the chemical composition of gladiolus plants. Microbein biofertilizer (M.B.)…”
Section: Introductionmentioning
confidence: 87%